Elucidating the Role of Nrf2 Signaling Pathway in Mycoplasma Infections - Sarmistha Saha; Nadezhda Sachivkina; Olga Kuznetsova; Ekaterina Neborak; Natallia Zhabo (Frontiers in Bioscience-Landmark)
Mycoplasmas are the smallest cell-wall-less self-replicating prokaryotes. Mycoplasma species can be found within and outside cells as “silent parasites” that live intracellularly and as membrane surface parasites. The pathogen’s impact on respiratory health seems primarily caused by its capacity to alter immune responses, cause airway inflammation, and damage epithelial barriers. Much progress has been made in understanding Mycoplasma-induced inflammation and oxidative stress. However, there are still issues in therapeutic management, such as the development of strains that are resistant to antibiotics, the shortcomings of the available diagnostic techniques, and possible long-term respiratory consequences. On the other hand, to combat oxidative stress, inflammation, and metabolic abnormalities, activation of the transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2) is becoming a more appealing therapeutic strategy. Nrf2 activation coordinates a thorough defense through its transcriptional targets, enabling adaptability and survival under a variety of cellular stressors. Nrf2 is regarded as a therapeutic target, and pharmacological Nrf2 activators have demonstrated protective effects in multiple pathological consequences and advantages in clinical trials. In this review, we discussed the rationale for targeting Nrf2 in a series of inflammatory responses caused by Mycoplasma species.